Polymer Materials for U-Shaped Optic Fiber Sensors: A Review - Patryk Sokołowski; Jacek Łubiński; Paweł Wierzba; Jakub Czubek; Piotr Miluski; Filip Janiak; Shanyue Guan; Małgorzata Szczerska (Photonics)
Fiber optic sensors have gained popularity over the last few decades. This is due to their numerous advantages, such as good metrological parameters, biocompatibility and resistance to magnetic and electric fields and environmental pollution. However, those built from glass fiber have one main disadvantage—they are fragile, meaning they can be easily damaged, even by the presence of vibration. Due to the great progress made by material research recently, it is possible to build such a sensor with polymer fibers instead. Although those fibers have worse transmission parameters compared to telecommunication fibers, they provide the possibility to realize flexible fiber optic sensors. Taking into consideration other advantages of such fibers, including biocompatibility, electromagnetic resistance and even, biodegradation characteristics, as well as there being a variety of materials we can use, it can be seen that those materials are beneficial to produce fiber optic sensors. This paper aims to provide researchers with guidelines on the factors to consider when choosing a material for bent fiber optic sensors, depending on the application.